Obstetric history of women with m.3243A>G: an observational cohort study - Kuikka, Petra; Nikkinen, Hilkka; Majamaa, Kari; Martikainen; Mika; Henrik (BMJ Publishing Group, 2026)
Background:
​​​​​​​Mitochondrial diseases are genetic disorders arising from pathogenic variants in nuclear or mitochondrial DNA (mtDNA) characterised by respiratory chain dysfunction. Clinical manifestations are diverse, and treatment is mostly symptomatic. Mitochondria are maternally inherited, but new reproductive technologies may prevent the transmission of pathogenic mtDNA. We decided to investigate the pregnancies of women with the m.3243A>G mtDNA variant.
Methods:
16 women with m.3243A>G were included in this retrospective, observational cohort study. Medical records were screened for pregnancies managed at Oulu University Hospital (Oulu, Finland) during the years 1960–2020. Main outcomes were obstetric complications as well as maternal and neonatal morbidity. All eligible pregnancies (n=38) were reviewed for the course of pregnancy and delivery as well as maternal and neonatal health.
Results:
The median of maternal m.3243A>G load in muscle or buccal epithelium was 59% (range 30–76%). There were 30 deliveries and 31 born children. Among singleton pregnancies, gestational diabetes was present in seven (24%), gestational hypertension or pre-eclampsia in three (10%) and preterm delivery in two (7%). Mean birth weight was 3537 g (1020–5310 g), with a z-score of 0.80±1.37 for girls and 0.77±1.05 for boys. Seven newborns (12%) were treated in the neonatal intensive care unit.
Conclusion:
Women harbouring m.3243A>G may have an elevated risk for obstetric complications, such as gestational diabetes and gestational hypertension. Their babies may have an elevated risk of preterm birth and need for intensive care. Pregnancies of women with m.3243A>G should be followed carefully.